Unequal family lives : causes and consequences in Europe and the Americas - Cahn, Naomi (Cambridge : Cambridge University Press, 2018)
Across the Americas and Europe, the family has changed and marriage is in retreat. To answer the question of what's driving these changes and how they impact social and economic inequality, progressives have typically focused on the economic causes of changing family structures, whereas conservatives tend to stress cultural and policy roots. In this illuminating book, an international group of scholars revisit these issues, offering competing and contrasting perspectives from left, center, and right, while also adding a third layer of analysis: namely, the role of gender - changes in women's roles, male employment patterns, and gendered family responsibilities - in driving family change across three continents. Unequal Family Lives: Causes and Consequences in Europe and the Americas adds richness and depth to our understanding of the relationship between family and economics in the United States, Europe, and Latin America. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 01 Aug 2018).
Open Access title.
Keywords: Families -- United States; Families -- Europe; Families -- Latin America; Income distribution -- United States; Income distribution -- Europe; Income distribution -- Latin America